BSN Programming Frameworks - Fortino, Giancarlo; Gravina, Raffaele; Galzarano, Stefano (Wearable Computing, 2018)
This chapter investigates the problems and challenges involved in programming body sensor networks (BSNs). It discusses the importance of adopting high‐level programming abstractions and software tools through which developers are able to overcome the difficulties in managing such distributed and resource‐constrained embedded environments. Moreover, the chapter provides the state‐of‐the‐art of middleware and programming frameworks by focusing on both capabilities and lack of proper functionalities needed for facing today's and future challenges in BSN application development. It also discusses the programming issues in sensor networks, with particular regard to the methodologies for efficiently and effectively building applications on BSNs. The chapter focuses on the most common programming abstractions provided in the literature by highlighting their main peculiarities and features and their applicability in the BSN domain. Furthermore, it explores the requirements for designing effective BSN‐specific frameworks. Finally, it briefly describes the current available frameworks for developing BSN applications.